Racial inequality in the trauma of women: A disproportionate decade. Issue 1 (July 2020) - Izadi, Shawn N.; Patel, Niral; Fofana, Demba; Paredes, Anghela Z.; Snyder, Samuel K.; Torres-Reveron, Annelyn; Skubic, Jeffrey J.
Abstract : BACKGROUND: Historically, women have been largely underrepresented in the body of medical research. Given the paucity of data regarding race and trauma in women, we aimed to evaluate the most common types of traumas incurred by women and analyze temporal racial differences. METHODS: A 10-year review (2007–2016) of the National Trauma Data Bank was conducted to identify common mechanisms of injuries among women. Trends of race, intent of injury, and firearm-related assaults were assessed using the Cochran-Armitage Trend test. Multivariable multinomial logistic regressions were utilized to examine the association between race and trauma subtypes. RESULTS: Of the 2, 082, 768 women identified as a trauma during this study period, the majority presented due to an unintentional intent (94.5%), whereas fewer presented secondary to an assault (4.4%) or self-inflicted injury (1.1%). While racioethnic minority women encompassed a small percentage of total traumas (19%), they accounted for roughly three fifths of assault-related traumas ( p < 0.001). Though total assaults decreased by 20.8% during the study period, black and Hispanic women saw a disproportionately smaller decrease of 15.1% and 15.8%, respectively. On regression analysis, compared with white women, black women had more than four times the odds of being an assault-related trauma compared with unintentional trauma (odds ratio, 4.48; 95% confidence interval, 4.41–4.55). On subset analysis, firearm-related assault was 17.3 times more prevalent among black women (white, 0.3% vs. black: 5.2%; p < 0.001). In fact, history of alcohol abuse was found to be an effect modifier of the association of race/ethnicity and firearm-related trauma. CONCLUSION: Compelling data highlight a disproportionate trend in the assault-related trauma of minority women. Specifically, minority women, especially those with a history of alcohol abuse, were at increased risk of being involved in a firearm assault. Further studies are essential to help mitigate disparities and subsequently develop preventative services for this diverse population. LEVEL OF EVIDENCE: Epidemiological, Level III.